THE EFFECT OF USING COLLABORATIVE STRATEGIC IN READING NARRATIVE TEXT AT SMA ADVENT 2 MEDAN - Ricki Asi Erwindo Siahaan; Rani Rakasiwi; Masriani Mery Rosmida Silalahi (INFOKUM, 2022)
Language is very important to all of people, because language is use for communication with other, without language we shall find difficulties to get something and communication with another people. it means that without comprehending the language, someone will get many difficulties in lives. The objective of the study is to find out what is the effect of using collaborative strategic in reading narrative text at SMA Advent 2 Medan. The scope the research is focus on students grade one at SMA Advent 2 Medan to improve their ability in reading comprehension on narrative text. The method uses in this research is quantitative research. Quantitative research is defined as a the systematic investigation phenomena by gathering. The pre-experimental research with one group pre and post-test design was used to conduct this study. In this research, the researcher used the pre-test and post-test to know the students’ achievement in their writing performance